cGMP Signalling in Smooth Muscle Cells of the Vasculature and the Male Reproductive Tract - Rager, Christine Angelika; Justus Liebig University Giessen (My University, 2025)
Numerous therapeutics target the relaxation of smooth muscle. A signalling molecule that plays a decisive role in this process is cyclic guanosine monophosphate (cGMP). Most knowledge about the cGMP signalling system has been generated based on cell culture. Lately, conclusions regarding smooth muscle physiology based purely on in vitro data have been highly debated. Especially for vascular smooth muscle cells, which are characterized by high plasticity, drastic changes under cell culturing condition have been shown, by which the cGMP system, among others, seems to be strongly affected. Since the culture-induced modification of the cell genotype involves various reference genes, the comparison between in vivo and in vitro is often found to be difficult. The aim of this work was therefore to find a reference gene that allows the direct comparison of aortic smooth muscle cells in the intact vessels versus culture at the gene expression level, and ideally enable the characterization of sex-dependent differences. Subsequently, the reference gene U2 was then used to compare the expression of the natriuretic peptide receptors (GC-A, GC-B, NPRC) and the receptor for nitric oxide (sGC) in intact tissue versus cell culture and four receptors which are known to significantly regulate the intracellular cGMP level were investigated. The comparison showed a drastic change in the expression profile of the aortic cells in culture. With the exception of Gc-a, which maintained a stable expression level, the expression of all receptors increased dramatically in cell culture. It can be suggested that this difference probably leads to a disturbance of cellular cGMP homeostasis due to a shift in the ratio of the receptors to each other. Since antibodies, especially for the natriuretic peptide receptors, still do not allow satisfactory detection, the gene expression data were confirmed at the functional level using cGMP ELISA. No significant differences between the two sexes could be detected besides a higher fluctuation range of the data points in females. This could suggest a cycle-related regulation of the cGMP system. The second part of this thesis focused on smooth muscle cells in the male reproductive tract. Contrary to the vascular chapter of this work, only intact tissue was used for the investigations. In the testis, smooth muscle cells surround the germinal epithelium of the seminiferous tubules in which the sperm are produced. Here the smooth muscle cells play an important role in transporting the seminal fluid and the spermatozoa it contains through the tubular lumen towards the epididymis. To ensure this directed transport, the superficial muscle layer of the testicular tubules contracts. A hypothesis based on preliminary results of this work suggests that the intensity of contraction is precisely coordinated with the spermatogenesis in a timely manner. The aim of the second chapter of this thesis was therefore to establish a method to detect spontaneous contractions and their alteration by relaxing and contracting substances and to evaluate these with regard to different stages of spermatogenesis. Using a previously tested method for live recording, seminiferous tubules of the rat were recorded before and after spermiation. For the evaluation, an analysis tool was adapted, that had previously been used in parasitology and involves the imaging tool FIJI. Using this tool, tissue contractions could be differentiated in terms of their general intensity, amplitude and frequency. It was shown that the seminiferous tubules before and after spermiation differ drastically with regard to their spontaneous contraction behaviour. Further experiments also showed that these contractions could be attenuated to the same extent by treatment with nitric oxide and, interestingly, also by noradrenaline. The extent to which treatment with relaxing (nitric oxide) and contracting (noradrenaline) stimulants influences the different parameters of the contractions (intensity, amplitude, frequency) requires further investigation in order to develop the FIJI-based analysis method for pharmacological/diagnostic purposes in the future.
Keywords: ddc:610